2018
DOI: 10.1002/ente.201700855
|View full text |Cite
|
Sign up to set email alerts
|

Ba‐doping to Improve the Cycling Stability of LiNi0.5Mn0.5O2 Cathode Materials for Batteries Operating at High Voltage

Abstract: LiNi0.5−xBaxMn0.5O2 (x=0, 0.03, 0.05, 0.08) samples were prepared by using a combination of co‐precipitation and solid‐state methods. All of the cathode materials were analyzed by inductively coupled plasma mass spectrometry (ICP‐MS), X‐ray diffraction (XRD), Rietveld refinement, X‐ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The results of them show that we have successfully prepared the target materials, and Ba‐doping can keep the structure stable and lower Li/Ni cation mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…[ 56 ] Yin and co‐workers reported that partial Ba‐doping in the Li[Ni 0.5 Mn 0.5 ]O 2 structure improved the structural stability and reduced the Li + /Ni 2+ cation mixing. [ 57 ] Specifically, Ba 2+ is an attractive dopant or substituent owing to its higher bond dissociation energy of the BaO bond (562 kJ mol −1 ) than that of the NiO bond (382.0 kJ mol −1 ) (Figure 4b). [ 58 ] Li and co‐workers suggested that Mg 2+ ‐doped Li[Ni 0.45 Mg 0.05 Mn 0.5 ]O 2 displays enhanced cell performance because the inert Mg 2+ acts as a pillar to stabilize the layered structure.…”
Section: Co‐less Ni‐rich Cathodes Of Pastmentioning
confidence: 99%
“…[ 56 ] Yin and co‐workers reported that partial Ba‐doping in the Li[Ni 0.5 Mn 0.5 ]O 2 structure improved the structural stability and reduced the Li + /Ni 2+ cation mixing. [ 57 ] Specifically, Ba 2+ is an attractive dopant or substituent owing to its higher bond dissociation energy of the BaO bond (562 kJ mol −1 ) than that of the NiO bond (382.0 kJ mol −1 ) (Figure 4b). [ 58 ] Li and co‐workers suggested that Mg 2+ ‐doped Li[Ni 0.45 Mg 0.05 Mn 0.5 ]O 2 displays enhanced cell performance because the inert Mg 2+ acts as a pillar to stabilize the layered structure.…”
Section: Co‐less Ni‐rich Cathodes Of Pastmentioning
confidence: 99%
“…Element doping is an efficacious strategy to enhance the electrochemical properties of cathode materials. Numerous elements have been attempted to dope into LiNi 0.5 Mn 0.5 O 2 , such as Al [29,30], Mg [31], Ba [32], Cu [33], Sb [34], Ti [35], Zr [36], Si [37], Mo [38] and F [39]. All these doping ions can suppress the Li/Ni cation mixing in LiNi 0.5 Mn 0.5 O 2 , and further improve the rate capability, specific capacity, and cycling performance.…”
Section: Layered Mn-based Oxidesmentioning
confidence: 99%
“…This is because Al doping could narrow the size distribution and decrease Li + migration resistance with extended lattice parameter of c axle. Ba doping can effectively promote the cycling performance of LiNi 0.5 Mn 0.5 O 2 because the Ba-O bond has a greater dissociation energy than the Ni-O bond (563 kJ mol -1 vs. 391.6 kJ mol -1 ), which helps to stabilize the crystal structure [32]. As a result, after 100 cycles, Ba-doped LiNi 0.5 Mn 0.5 O 2 can still operate at 97% of its initial specific capacity.…”
Section: Layered Mn-based Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the resultant strong Ba–O (563 kJ mol −1 ) and Al–O (512 kJ mol −1 ) bonds can effectively stabilize the lattice O. 21,24 These merits endow BA-NCM85 with superior rate ability and cycle stability.…”
Section: Introductionmentioning
confidence: 99%